(untitled) (Revista cientifica In Vestigium Ire, 2021)
The characteristics of the Hass avocado value chain in Silvania Cundinamarca is the propitious setting for agricultural producers to strengthen their production processes and activities through initiatives and programs supported by government entities, associations, export companies, and agribusiness. The objective of the research allowed to diagnose, characterize and design the value chain of the Hass avocado “Persea americana” in Silvania. The methodological construction was carried out through farm surveys, observation, structured interviews, dialogue with the community, to determine socioeconomic and biophysical characteristics and the PEYEA matrix to generate strategies. Within the results of I identify, characterize and design the value chain which is integrated by the production, commercialization, export and final consumer links. It is concluded that the Hass avocado production chain is relevant for the generation of alliances between the different actors in the chain, as well as its own productive benefit. Likewise, it is necessary to increase techniques of good agricultural practices to reduce energy, resources and regulate investment in production, therefore, it is necessary to adopt strategies for the sustainable management of natural resources along with the implementation of agroecological practices.